2000
DOI: 10.1007/s001340050014
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive critical incident monitoring in a neonatal-pediatric intensive care unit: experience with the system approach

Abstract: CIs are very common in pediatric intensive care. Knowledge of them is a precious source for quality improvement through changes in the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
1
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 14 publications
8
72
1
10
Order By: Relevance
“…This agrees with other studies that reported that failure in medical devices was one of the causes of near misses in the NICU (26,27).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with other studies that reported that failure in medical devices was one of the causes of near misses in the NICU (26,27).…”
Section: Discussionsupporting
confidence: 93%
“…This agrees with a study that reported 61% minor errors, 26% moderate errors and 13% major errors (11). However, our results disagree with another study that reported 30% major errors (death or need for ICUspecific intervention), 25% moderate errors (requiring routine therapy available outside the ICU) and 45% minor errors (no intervention required) (27).…”
Section: Discussionsupporting
confidence: 70%
“…Transcription errors were not commonly reported within paediatric studies, with only three articles acknowledging their incidence [Frey et al 2000[Frey et al , 2002Fortescue et al 2003]. These types of errors made up 5.8% of all medication errors, and included: punctuation mistakes (i.e.…”
Section: Paediatricmentioning
confidence: 99%
“…writing '3' instead of '0.3'), omission of medication, wrong unit of measurement (i.e. g instead of mg) and incorrect doses [Frey et al 2000[Frey et al , 2002Fortescue et al 2003]. …”
Section: Paediatricmentioning
confidence: 99%
“…When formatted as a nonhierarchical tool inviting contributions from all staff levels, the morbidity and mortality conference plays a key role in the system approach to medical errors. (Pediatr Crit Care Med 2016; 17:67-72) Key Words: adverse events; error and risk analysis; medical error; morbidity and mortality conference; patient safety; pediatric intensive care unit T he morbidity and mortality conference (MMC) served traditionally as an educational aid for medical trainees, but more recently, new emphasis has been placed on patient safety and quality improvement (1)(2)(3)(4)(5)(6)(7)(8), including critical incident monitoring (9), error and risk analysis (10), postincident team debriefings, and the monitoring of quality indicators and adverse events (11). By identifying adverse events and their cause(s), the MMC prompts intervention and may prevent patient harm (8,12,13).…”
Section: Measurements and Main Resultsmentioning
confidence: 99%